1995
DOI: 10.1002/jbmr.5650100613
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent cyclical etidronate treatment maintains the mass, structure and the mechanical property of bone in ovariectomized rats

Abstract: We examined the mechanical properties of rat bones treated with etidronate intermittent cyclic treatment (etidronate-ICT). Fifty Fisher rats, 7 months of age, underwent ovariectomy (OVX; n = 40) or sham operation (n = 10). The OVX rats were assigned to 4 groups injected with etidronate at the respective dose of 0, 2, 4, or 8 mg/kg of body weight (bw) 5 days each week for 2 weeks, followed by a 10-week period of no treatment. This regimen was repeated for 48 weeks. At the end of the treatment period, the ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Katsumata et al 23 and Shen et al 3 observed a decrease of bone mineral content and density in the femur of ovariectomized rats compared to the intact group, but there was no difference between groups in terms of fracture resistance or rigidity. Wang et al 25 evaluated the influence of osteoporosis on the middle and late periods of tibia fracture healing in ovariectomized rats, analyzing histomorphological changes, bone mineral density and biomechanical properties.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Katsumata et al 23 and Shen et al 3 observed a decrease of bone mineral content and density in the femur of ovariectomized rats compared to the intact group, but there was no difference between groups in terms of fracture resistance or rigidity. Wang et al 25 evaluated the influence of osteoporosis on the middle and late periods of tibia fracture healing in ovariectomized rats, analyzing histomorphological changes, bone mineral density and biomechanical properties.…”
Section: Discussionmentioning
confidence: 96%
“…However, an increase in bone strength and rigidity does not necessarily indicate improvement in the biomechanical properties of bone tissue 23 . We therefore used a three-point bending biomechanical test.…”
Section: Discussionmentioning
confidence: 96%
“…During data analysis, the femur was divided into 20 equal segments along its major axis. The mean values of BMD for the six most proximal scanned areas (1)(2)(3)(4)(5)(6), those for the next eight scanned areas (7)(8)(9)(10)(11)(12)(13)(14), and those for the six most distal areas (15)(16)(17)(18)(19)(20) were…”
Section: Measurement Of Bone Mineral Densitymentioning
confidence: 99%
“…The relative rates of resorption and formation on the periosteal and endocortical surfaces would affect the cortical width, total area, and moment of inertia, and thus bone strength [40]. An increase in periosteal bone formation rate has resulted in increased bone strength due to an increased moment of inertia [1921, 41]. However, in prepubescent animals that receive GnRH-a injections, the increased periosteal formation did not rescue bone strength [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, increased femoral periosteal circumference and moments of inertia have been reported after ovariectomy [19, 20]. As a result, mechanical strength after ovariectomy may not decrease and has actually been reported to increase in some studies [1921]. These data support the hypothesis that suppressed estradiol should result in stronger bone; however, an animal model of delayed puberty (suppressed estrogen levels) has reported short-term decreases in peak moment and stiffness without changes in total area or bone area [22].…”
mentioning
confidence: 99%